But is it Innovation?: The Development of Novel Methodological Approaches in Qualitative Research. Issue 1 (April 2013) - Wiles, Rose; Bengry-Howell, Andrew; Crow, Graham; Nind, Melanie
Focusing on three case studies of novel approaches about which claims of innovation have been made, this paper explores the process of methodological innovation and the response of the social science community to innovations. The study focuses on three specific innovations: 'netnography', 'child-led research' and 'creative methods' and draws on interview data with researchers who have developed these approaches and those who have engaged with them. Data are explored through the lens of the social context of contemporary qualitative research methods and specifically what has been referred to in the UK as the 'impact' agenda. We argue that while methodological innovation may be viewed by researchers as important for the continued success of social science disciplines, the processes whereby new methods are developed and marketed, within the context of contemporary social research and the impact culture, may limit their acknowledgement and acceptance within the broader social science community. This culture increases the speed at which innovations are developed and marketed, encourages the dissemination of codified or procedural approaches to innovations which limit the craft of qualitative research and encourages early career researchers to adopt approaches without being reflexive about the affordances these methods might provide.